RETENSI NASABAH DITELAAH DARI LAYANAN MOBILE BANKING DAN KEPERCAYAAN NASABAH - Mukti, Mukti; Arma, Aulia; Rahmadi, Rahmadi; Triasningrum, Frida Widyawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
BTPN Syariah is a dedicated bank for fulfilling customer needs and making an effort to increase the quality of its services. The problem in this study is that there has been a decline in customer retention, which is indicated by the increasing number of savings accounts that have not had the last transaction for more than 6 months in the period 2023 - 2024, this indicates a decline in customer trust in banking services provided by BTPN Syariah, where a decline in customer trust can reduce customer retention. The purpose of this study is to test and analyze the influence of mobile banking services and customer trust in customer retention Population in study This is BTPN Syariah KC Berau customers totaling 97 people. Engineering sampling in study This uses random sampling. Tool analysis in this study covers test instrument (test validity, test reliability), test assumption classic (test normality, test multicollinearity, test heteroscedasticity), multiple linear regression, test hypothesis through test t, test F, and test coefficient determination. Results of this study prove that variable mobile banking services have a significant influence on customer retention. This is show with mark coefficient regression as big as 0.259 . Whereas For mark count ( 2 , 640 ) > table (1,661)And sign (0.0 10 ) < sign a (0 ,05 ). The results of this study show that customer trust variables have a significant influence on customer retention. This is shown with mark coefficient regression of 0.292 . While For mark tcount (2, 723 ) > table (1,661) And sign ( 0.008 ) > sign a (0 ,05 ). Conclusion study This is mobile banking services have a positive influence on customer retention. Direction coefficient regression positive shows existence positive influence mobile banking services to customer retention, so that Hypothesis 1 is accepted. Customer Trust influences Customer retention. Direction coefficient regression positive shows existence influence positive customer trust to customer retention, so that hypothesis 2 is accepted. Share Researcher Furthermore, in order to be able to add another variable To understand more in mechanisms involved in influencing mobile banking services and customer trust to retain customers. Suggested variables are: halal perception, influencers